Discrimination of the bumble bee species Bombus occidentalis Greene and B. terricola Kirby by morphometric, colour and RAPD variation - Owen, Robin E.; Whidden, Troy L. (Zootaxa, 2013)
The taxonomic status of B. terricola Kirby and B. occidentalis Greene has long been questioned. However recent COI gene sequence data suggests that B. occidentalis and B. terricola do represent good biological species. In this paper we test the hypothesis that B. terricola and B. occidentalis are conspecific by using independent morphometric and genetic (RAPD) data. For comparison we also analyzed one consubgeneric species, B. moderatus (now B. crytptarum), and one non-consubgeneric species B. (Pyrobombus) perplexus. Discriminant function analysis of wing morphometric data correctly classified over 85% of the specimens of B. occidentalis and B. terricola. Analysis of molecular variance of the RAPD data showed a significant difference (P < 0.0001) between B. occidentalis and B. terricola. Colour variation from laboratory reared colonies of B. occidentalis suggests that probably two gene locus inheritance is likely but that hybridization as the sole basis for the colour variation seen in the nominate taxon B. occidentalis can be excluded. We conclude that B. terricola and B. occidentalis should be regarded as distinct species which have recently diverged, and that they can be distinguished by wing morphometrics and RAPD genotypes. Where they are sympatric (e.g. in Alberta) colour pattern variation is confined to B. occidentalis.